Dual-structure microwave-assisted magnetic recording using only a spin torque oscillator - Greaves, Simon John; Saito, Waka (AIP advances, 2019)
The selective switching of dual-structure magnetic dots under the influence of the stray field from a spin torque oscillator was investigated. A configuration was found which allowed selective switching of either structure when subject to ac magnetic fields oscillating at 9 GHz and 20 GHz. No other external magnetic fields were needed to switch the magnetisation of the structures.